(untitled) (American Journal of Islam and Society, 2006)
European Trade and Colonial Conquest is authored by Biplab Dasgupta, a renowned political and social activist from Calcutta who taught economics at Calcutta University and was a member of the Parliament of India for several years. He has authored many books on various aspects of India’s socioeconomic and political life in the post-independence era, such as the oil industry, the Naxalite movements, trends in Indian politics, labor issues and globalization, agrarian change and technology, rural change, urbanization, and migration. The present book primarily focuses on the evolution of Bengal’s economy and society over the precolonial period, beginning from prehistoric days. Even though there are writings on Bengal’s colonial history, we know very little about its precolonial past except for the names of kings, the chronology of dynasties, and scattered references to urban settlements. Dasgupta shows a specific interest in highlighting the socioeconomic history of the last two and half centuries, from Vasco de Gama’s journey to India in 1498 to the battle of Palashi in 1757. The author asserts that he explores in detail the socioeconomic and political context of Bengal that facilitated the transfer of power to European hands, because historians generally ignore this rather quite long and critical period. He, therefore, comments that this is “less a book on pre-colonial Bengal” and more a book on European trade and colonial conquest (p. vii). The book explains how European commercial enterprise in Bengal gathered political power through its control over trade and gradually transformed itself into a colonial power. Although the Mughals held political power during this period, the economic power and control of the Indian Ocean trade routes were gradually slipping into European hands. It is believed that Clive’s victory at the battle of Palashi led to the colonial conquest of Bengal. However, focusing on Bengal’s socioeconomic ...